(untitled) (The Pakistan Development Review, 2003)
Pakistan is fortunate enough because its soils, topography and climate are generally suitable for farming but its agriculture sector faces the problem of scarcity of the irrigation water. This paucity of irrigation supplies has forced the farmers to use the ground water to augment their surface supplies. The quality of ground water in Pakistan varies from fit for irrigation to moderately saline to sodic. Thus the tubewell owners in the marginal quality ground water areas are bound to use the tubewell water in conjunction with the surface water on their farms. Currently the farmers are using about 65.75 BCM of ground water in Pakistan [Halcrow (2002)]. The international literature is filled with the studies on conjunctive water management and its impact on crop productivity and related issues [Gangwar and Toorn (1987); Bredehoeft and Young (1983); Gorelick (1988); Lingen (1988); O’Mara (1988); Shah (1988); Brewer and Sharma (2000); Datta and Dayal (2000); Raju and Brewer (2000); Sakhtivadivel and Chawala (2002) and Chaudhary and Shah (2003)]. In Pakistan, the review of literature shows that all of the previous studies conducted in the arena of water management reported the management problems leading to the inefficiencies in irrigation application and reduction in crop productivity, [Kijne and Velde (1991); Mustafa (1991) and Siddiq (1994)]. Few of the studies took into consideration the impact of waterlogging and salinity on productivity at farm level [Meyer, et al. (1996); Prathaper, et al. (1997) and O’Connell and Khan (1999)]. None of these studies have taken into consideration the trade-offs between gross farm income, ground water and salinity at irrigation subdivision level.